Pemanfaatan Gadget oleh Siswa SMA - Hermawan, Akhmad Rifqi; Kurniawan, Kusnarto (Universitas Negeri Semarang, 2017)
This research is conducted based on the phenomenon found in the interview with counseling teacher of Senior High School in Grobogan. It showed that the case relate with the use of gadget. The objective of the research is to find out the use of gadget by senior high school students based on the benefit and time. This research is survey research. High school students in Grobogan are the population of the research with 138 samples. Sampling two stage cluster proportional random sampling is the technique used in this research. The method used to collect the data is by using questionnaire and analysed by percentage descriptive technique. The result showed that 66,04% are positive in using gadget, the frequency of using/benefits of gadget in the questionnaire answer showed 65,84% of positive criteria. The frequency of using gadget based on the time using showed 90,02% of positive criteria. Overall, based on the result it also can be stated that the high school students in Grobogan use the gadget wisely and well.